The development of ethical skills for students of social work at Spanish universities. - Cuenca Silvestre, Mercedes; Parra Ramajo, Belén; Pastor Seller, Enrique (Social Work Education, 2025)
This article presents the results from a study that analyzed the length, content, and emphasis of ethics education taught in Social Work degrees at Spanish universities. The universities that offer this degree were identified (37), and the ethics courses in these course programs were analyzed using the corresponding course guides (27) and the specific skills identified in those course guides (175). Our results identified 14 specific skills. From a content analysis, it is evident that the ethics education that future social workers receive appears to be inadequate with respect to the challenges they will face in different areas of intervention and professional work. Ethics courses currently taught at Spanish universities seems inadequate to provide sufficient abilities and professional skills for the ethical practice of Social Work. This study identified the contribution of ethics education to the field of Social Work in the current context of complexity and superdiversity.